Analysis of online learning difficulties in biology learning at Senior High School - Baiq Indah Komalasari; Dadi Setiadi; Muhammad Yamin (Jurnal Pijar Mipa, 2023)
Research on online learning difficulties during the COVID-19 pandemic has been carried out. The aim is to describe the process and learning difficulties while online learning. This research is descriptive and qualitative. Sampling is done in three ways: interviews, questionnaires, and documentation. The data obtained is reduced, presented, reviewed, and then conclusions are drawn. As a result, the difficulties experienced by students during the process of learning online, namely the difficulty in using WhatsApp and chat group entry, make students unable to focus on learning, difficulties in the form of signals, and learning disabilities-line is a difficulty that is often experienced, learning is difficult because of signal constraints and wasteful internet quota. In conclusion, online learning difficulties are the inability of students to use learning applications such as What tApp, Google Classroom, Google Meet, and Zoom meetings. Some factors that make learning difficult are constrained by unstable signals and a lack of communication between students and teachers.